Resilient to Stress: Proposed a Novel Type E Personality - Lee, Hyun-ju; Shim, Insop; Pyun, Kwang Ho (Seuteureseu yeon-gu (Online), 2017)
Stress responses vary with individual differences in sensitivity to stressful stimulus. Individuals withstress susceptible personalities are facing an increased risk for developing various stress-relateddiseases. Epigenetic mechanisms, gene variants and personality are the key factors associated withindividual differences. Although many studies have reported stress susceptible personalities and stressresilient personality, its underlying neural and hormonal mechanism have not been investigated yet. In this study we propose a new type E personality which turns stressful stimulus into eustress bypositive perspectives. Type E personality, characterized by optimistic perspective, gratitude, charitywork, social support, altruistic, religious activities and affective communication is closely associatedwith enhancing stress resilience through modulating immune, neuronal and endocrine systems. KCI Citation Count: 0